2020
DOI: 10.26773/jaspe.200101
|View full text |Cite
|
Sign up to set email alerts
|

A Time Motion and Analysis of Partnering Skills in Latin-American Dance Using a Semi-Automatic Tracking System: A Case Study

Abstract: The aim of the research was analysing motion and partnering skills by examining different relation positions between dance partners, distance covered and speed of movement in Latin-American dance. The sample consisted of three elite Latin-American dance couples simultaneously danced each of five Latin dances consecutively. Dances were recorded using two cameras-first was used to determine the path of the dancers' movement (secured to the ceiling of the hall), the second camera was located on the side of the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The trajectory of the waltz is a wide movement in space, primarily in a circle. 1 The most salient characteristic of ballroom dance is its closed-hold position 2 in which the upper body segments of the male and female dancers are connected. Partnering is essential when dancing in the closed-hold position.…”
mentioning
confidence: 99%
“…The trajectory of the waltz is a wide movement in space, primarily in a circle. 1 The most salient characteristic of ballroom dance is its closed-hold position 2 in which the upper body segments of the male and female dancers are connected. Partnering is essential when dancing in the closed-hold position.…”
mentioning
confidence: 99%
“…Ballroom dancers move closely with their partner, maintaining a right trunk rotation towards the partner, 28 a hand-hold position during their movement across the floor. 34 The hold technique ideally has to be held in a static position from elbow to elbow in the horizontal plane; otherwise the artistic performance may be compromised. Couples performing in Standard dancing, train this hold technique during many hours per week.…”
Section: Discussionmentioning
confidence: 99%
“…The technical feature of Latin dance is to complete various technical movements with the cooperation of. Therefore, in the analysis of the time characteristics of the movements, it is necessary to describe and summarize in combination with the melody, time value, speed and other aspects of the performance style [3][4]. Through comprehensive analysis, it is concluded that the movement time characteristics of amateur youth in Latin dance are mainly manifested in the rhythmicity, separability and mobility of movements [5].…”
Section: Introductionmentioning
confidence: 99%